2020
DOI: 10.1007/s13205-020-02369-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors: frontiers in rapid detection of COVID-19

Abstract: The rapid community-spread of novel human coronavirus 2019 (nCOVID19 or SARS-Cov2) and morbidity statistics has put forth an unprecedented urge for rapid diagnostics for quick and sensitive detection followed by contact tracing and containment strategies, especially when no vaccine or therapeutics are known. Currently, quantitative real-time polymerase chain reaction (qRT-PCR) is being used widely to detect COVID-19 from various types of biological specimens, which is time-consuming, labor-intensive and may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
142
0
8

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 82 publications
0
142
0
8
Order By: Relevance
“…Furthermore, potentiostats are already available in miniaturized formats, enabling the possibility of on-the-spot or point-of-care applications. Electrochemical biosensors have previously been used to detect viral antigens from several pathogenic viruses such as Hepatitis, Dengue, Rabies, and Zika [ 16 , 17 , 18 ]. The ongoing COVID-19 pandemic has led to an increase in biosensor research aiming to identify and quantify SARS-CoV-2 specific antigens [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, potentiostats are already available in miniaturized formats, enabling the possibility of on-the-spot or point-of-care applications. Electrochemical biosensors have previously been used to detect viral antigens from several pathogenic viruses such as Hepatitis, Dengue, Rabies, and Zika [ 16 , 17 , 18 ]. The ongoing COVID-19 pandemic has led to an increase in biosensor research aiming to identify and quantify SARS-CoV-2 specific antigens [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors have been shown to be capable of attaining detection limits in the fentomolar and attomolar range by tapping into the various types of signal amplification strategies. For a more comprehensive discussion on the potential application of different biosensing approaches for the detection of SARS-CoV-2, the review by Samson et al [ 167 ] is recommended. Biosensors at the proof-of-concept stage provide a glimpse of their potentials to revolutionize diagnostic testing, but the journey to commercialization remains long, costly and arduous.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…These types of sensors are fabricated by coating graphene sheets with a selective antibody against SARS-CoV-2 spike protein G. Seo et al [ 81 ] have reported a graphene FET device for the detection of the SARS-CoV-2 spike protein at concentrations of 1 fg/mL in phosphate-buffered saline and 100 fg/mL clinical transports medium. The detection of the virus in the air has also been claimed in this report [ 81 ].…”
Section: Diagnosismentioning
confidence: 99%
“…These types of sensors are fabricated by coating graphene sheets with a selective antibody against SARS-CoV-2 spike protein G. Seo et al [ 81 ] have reported a graphene FET device for the detection of the SARS-CoV-2 spike protein at concentrations of 1 fg/mL in phosphate-buffered saline and 100 fg/mL clinical transports medium. The detection of the virus in the air has also been claimed in this report [ 81 ]. Groltex and Sanford Burnham Prebys Medical Discovery Institute has claimed to develop a graphene-based biosensor platform consisting of handheld reader units and disposable plastic testing chips [ 82 ].…”
Section: Diagnosismentioning
confidence: 99%